2017
DOI: 10.1159/000475452
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Geriatric Assessment in the Care of Patients with Gastrointestinal Malignancies

Abstract: Background: The majority of patients with gastrointestinal (GI) malignancies are older. Recently, it has become evident that elements from a geriatric assessment (GA) are powerful predictors of outcomes such as postoperative morbidity and mortality, length of stay, type of treatment received, and survival across several GI tumor types in older adults. A GA is a systematic evaluation of functional status, comorbidities, polypharmacy, cognition, nutritional status, emotional status, and social support. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(43 reference statements)
3
3
0
1
Order By: Relevance
“…In terms of serious complications, the frail group had a higher incidence than the non-frail group. We also found that frailty has an important impact on the prognosis of patients with colorectal cancer, regardless of frailty screening tools, reported from multiple studies ( 24 26 ).…”
Section: Discussionsupporting
confidence: 57%
“…In terms of serious complications, the frail group had a higher incidence than the non-frail group. We also found that frailty has an important impact on the prognosis of patients with colorectal cancer, regardless of frailty screening tools, reported from multiple studies ( 24 26 ).…”
Section: Discussionsupporting
confidence: 57%
“…It is essential to perform geriatric assessments systematically in the preoperative work-up [ 43 45 ], pay attention to the concept of prehabilitation [ 46 ], and increase focus on patient preferences [ 47 ]. Recent reports have demonstrated the value of a geriatric assessment in summarizing the patient's degree of frailty and predicting postoperative morbidity and mortality for older patients with colon cancer [ 48 ]. The Society for Geriatric Oncology has recommended these assessments for all patients with cancer that are over 70 years of age [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 6 studies including 1,037 participants found that comorbidity, polypharmacy and activities of daily living (ADL) dependency components to the CGA were predictive factors for postoperative complications in gastrointestinal cancer patients (with cognition, nutritional status, depression and instrumental ADLs showing no conclusive relationship) (26). There have been limited studies evaluating the role of a GA in predicting outcomes specifically in gastro-oesophageal cancers, with most small retrospective cohort studies (27). The largest of these reviewed279 patients, in a single US centre, who had undergone gastrectomy for adenocarcinoma and in whom a GA had been performed within 30 days of surgery.…”
Section: Identifying Frail Older Patientsmentioning
confidence: 99%